Aflatoxin B1 Degradation and Detoxification by Escherichia coli CG1061 Isolated From Chicken Cecum - Wang, Lingling; Wu, Jun; Liu, Zhiwen; Shi, Yutao; Liu, Jinqiu; Xu, Xiaofan; Hao, Shuxian; Mu, Peiqiang; Deng, Fengru; Deng, Yiqun (Frontiers in Pharmacology, 2019)
Aflatoxin B1 (AFB1) is one of the most hazardous mycotoxins contamination in food and feed products, which leads to hepatocellular carcinoma in humans and animals. In the present study, we isolated and characterized an AFB1 degrading bacteria CG1061 from chicken cecum, exhibited an 93.7% AFB1 degradation rate by HPLC. 16S rRNA gene sequence analysis and a multiplex PCR experiment demonstrated that CG1061 was a non-pathogenic Escherichia coli. The culture supernatant of E. coli CG1061 showed an 61.8% degradation rate, whereas the degradation rates produced by the intracellular extracts was only 17.6%, indicating that the active component was constitutively secreted into the extracellular space. The degradation rate decreased from 61.8 to 37.5% when the culture supernatant was treated with 1 mg/mL proteinase K, and remained 51.3% when that treated with 100°C for 20 min. We postulated that AFB1 degradation was mediated by heat-resistant proteins. The content of AFB1 decreased rapidly when it was incubated with the culture supernatant during the first 24 h. The optimal incubation pH and temperature were pH 8.5 and 55°C respectively. According to the UPLC Q-TOF MS analysis, AFB1 was bio-transformed to the product C16H14O5 and other metabolites. Based on the results of in vitro experiments on chicken hepatocellular carcinoma (LMH) cells and in vivo experiments on mice, we confirmed that CG1061-degraded AFB1 are less toxic than the standard AFB1. E. coli CG1061 isolated from healthy chicken cerum is more likely to colonize the animal gut, which might be an excellent candidate for the detoxification of AFB1 in food and feed industry.